Marriage and Conflict: Conjugal Desertion, Divorce and Ecclesiastical Annulment in Modern Andalusia (Archbishopric of Seville, 18th Century) - Macías Domínguez, Alonso Manuel; Candau Chacón, María Luisa (Revista Complutense de Historia de América, 2016)
Despite new marriage regulations of the Council of Trent and the ratification of the indissolubility of the institution, conjugal realities clearly didn’t always follow proposed paths. In this article we approach matrimony as a locus of conflicts in which disagreements and problems of conviviality (including violence or infidelity) propitiated requests for separation or divorce (temporary or perpetual), ecclesiastical annulment and, contrarily as well, petitions for marital life. We analyze these lawsuits and trials within the context of the Archbishopric of Seville throughout the 18th century, without disregarding the historical context nor the possibilities afforded by Canon Law.
Keywords: Marriage Lawsuits; Divorce; Annulment; Conjugal Desertion; Council of Trent; Seville; Spain 18th century.